2014
DOI: 10.2147/cia.s56246
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits influencing somatization symptoms and social inhibition in the elderly

Abstract: PurposeSomatization is a common symptom among the elderly, and even though personality disorders have been found to be associated with somatization, personality traits have not yet been explored with regard to this symptom. The aim of this study is to investigate the relationship between personality traits and somatization, and social inhibition.Patients and methodsAs part of a cross-sectional study of a community sample, 126 elderly Thais aged 60 years or over completed self-reporting questionnaires related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Similarly, in a recent population survey of more than 5000 Swedish adolescents, Type D was associated with higher levels of self-reported psychosomatic symptoms, musculoskeletal pain, and sleep disturbance (Condén, Leppert, Ekselius, & Åslund, 2013;Condén, Rosenblad, Ekselius, & Aslund, 2014). Other somatic research has found that negative affectivity and social inhibition are also each independently associated with increased somatization and unexplained symptoms (Watson & Pennebaker, 1989;Wongpakaran & Wongpakaran, 2014). Because, even in healthy populations, Type D personality is associated with somatic complaints and exaggerated symptom reporting, we hypothesize that functional somatic syndromes, conditions that are characterized primarily by general somatic complaints of unclear etiology, such as chronic fatigue syndrome or fibromyalgia, may be more susceptible to the effects of Type D personality than illnesses of known etiology such as type 2 diabetes or arthritis.…”
Section: Type D Personality and Health Outcomesmentioning
confidence: 89%
“…Similarly, in a recent population survey of more than 5000 Swedish adolescents, Type D was associated with higher levels of self-reported psychosomatic symptoms, musculoskeletal pain, and sleep disturbance (Condén, Leppert, Ekselius, & Åslund, 2013;Condén, Rosenblad, Ekselius, & Aslund, 2014). Other somatic research has found that negative affectivity and social inhibition are also each independently associated with increased somatization and unexplained symptoms (Watson & Pennebaker, 1989;Wongpakaran & Wongpakaran, 2014). Because, even in healthy populations, Type D personality is associated with somatic complaints and exaggerated symptom reporting, we hypothesize that functional somatic syndromes, conditions that are characterized primarily by general somatic complaints of unclear etiology, such as chronic fatigue syndrome or fibromyalgia, may be more susceptible to the effects of Type D personality than illnesses of known etiology such as type 2 diabetes or arthritis.…”
Section: Type D Personality and Health Outcomesmentioning
confidence: 89%
“…The Symptom Checklist 90 (SCL-90), a 90-item self-reporting questionnaire, was used to evaluate the psychological status of the patients. The symptom severity of each item was assessed using a 5-Likert scale, in which “0” indicated “not at all” and “4” indicated “extremely.” 9 The included patients were divided into the healthy and unhealthy psychology groups, according to their SCL-90 scores. 10 The SCL-90 score exceeding 160 represented unhealthy status, while that of less than 160 represented the healthy status.…”
Section: Methodsmentioning
confidence: 99%
“…Somatization has been examined in relation to the Big Five personality profile and is, among adults, associated with a higher level of neuroticism and a lower level of agreeableness [12, 13]. The only study conducted in an older sample found that a higher level of somatization was associated with a lower level of emotional stability, dominance and vigilance in 126 community-dwelling healthy older persons [14].…”
Section: Introductionmentioning
confidence: 99%